Funciones ejecutivas en el Trastorno Espectro Autista: Una Revisión Actualizada - Cahuana Cuentas, Milagros Isela (2024)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder, beginning during childhood, characterized primarily by social communication challenges, and restrictive behaviours and interests. Various quantitative research studies suggest that said symptoms may be directly related to the performance of executive functions (EF). Therefore, the objective of this research paper was to review the relevant literature produced in the last twenty years. For the methodology, 48 articles in both English and Spanish from various academic repositories were used. The results provide an updated general overview of the diagnosis of ASD, neuropsychological and neuroanatomical profiles, with an emphasis on the specific performance of executive functions in individuals with this disorder. It was concluded that most of the research shows a functional impairment in the following executive functions: working memory, cognitive flexibility, planning, response inhibition, verbal fluency and design fluency. Future research is suggested to establish an executive function profile of ASD, which will lead to significant advances in early detection and intervention.